Acquaintance content and obviation - Anand, Pranav; Korotkova, Natasha (ZAS Papers in Linguistics, 2018)
This paper is about what Ninan (2014) (following Wollheim 1980) calls the Acquaintance Inference (AI): a firsthand experience requirement imposed by several subjective expressions such as Predicates of Personal Taste (PPTs) (delicious). In general, one is entitled to calling something delicious only upon having tried it. This requirement can be lifted, disappearing in scope of elements that we will call obviators. The paper investigates the patterns of AI obviation for PPTs and similar constructions (e.g., psych predicates and subjective attitudes). We show that the cross-constructional variation in when acquaintance requirements can be obviated presents challenges for previous accounts of the AI (Pearson 2013, Ninan 2014). In place of these, we argue for the existence of two kinds of acquaintance content: (i) that of bare PPTs; and (ii) that of psych predicates, subjective attitudes and overt experiencer PPTs. For (i), we propose that the AI arises from an evidential restriction that is dependent on a parameter of interpretation which obviators update. For (ii), we argue that the AI is a classic presupposition. We model both (i) and (ii) using von Fintel and Gillies’s (2010) framework for directness and thus connect two strands of research: that on PPTs and that on epistemic modals. Both phenomena are sensitive to a broad direct-indirect distinction, and analyzing them along similar lines can help shed light on how natural language conceptualizes evidence in general. Keywords: evidentiality, firsthand experience, knowledge, predicates of personal taste, subjectivity